If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + 2) = 1 Reorder the terms: 4(2 + 2x) = 1 (2 * 4 + 2x * 4) = 1 (8 + 8x) = 1 Solving 8 + 8x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 8x = 1 + -8 Combine like terms: 8 + -8 = 0 0 + 8x = 1 + -8 8x = 1 + -8 Combine like terms: 1 + -8 = -7 8x = -7 Divide each side by '8'. x = -0.875 Simplifying x = -0.875
| 9x^2-5xy-6y^2 | | (x-6)(4x^2+x-7)=0 | | -8+9+(-7)= | | 5(y-3)=7 | | (9x-1)(7x+4)=0 | | -7+8(-9)= | | 25=1+4x | | -7=-x+1 | | provecos(2x)=2cos^2x-1 | | 96=-7x-2 | | y-2=-3/8x | | v+12=27 | | x^2-2x-3 | | (7x-1)+(6x-7)= | | 3(z-4)=7z+4 | | 2x+5-3x+40 | | 5n25 | | 6y-9+3-1y= | | -√(18y^17)= | | 5x-11y+7x-3y-4x+2y= | | 12x-7+3x | | 16=25/6x-34 | | 5x-11y+7x-3y-4x+2y | | 5x-9y+9x-5y-3x+3x | | 5x-9y+9x-5y-3x+3x= | | 4+4x=5-5x+7 | | 6x=-13 | | 9-4xy+11x-2x-5-9xy= | | (2x-4)+(5x-6)= | | 5/3n=21 | | (5x^2-9x+1)-(8x+13)=0 | | 3x+5/9-2x-7/6=13 |